2016
DOI: 10.1124/dmd.116.069914
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotonic Pill Reduces Myocardial Ischemia-Reperfusion Injury via Increasing EET Concentrations in Rats

Abstract: Accumulating data suggest that epoxyeicosatrienoic acids (EETs) and 20-hydroxyeicosatetraenoic acid, both cytochrome P450 (P450) enzyme metabolites of arachidonic acid (AA), play important roles in cardiovascular diseases. For many years, the cardiotonic pill (CP), an herbal preparation derived from Salviae Miltiorrhizae Radix et Rhizoma, Notoginseng Radix et Rhizoma, and Borneolum Syntheticum, has been widely used in China for the treatment of coronary artery disease. However, its pharmacological mechanism ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…It is recognized the current study was limited by not directly assessing changes in the levels of epoxylipids (EETs, EDPs, EpOMEs) as well as the diol metabolites (DiHOMEs) in response to IR injury. However, it has been shown that cardiac ischemic insults decrease levels of the cardioprotective epoxylipids EETs and EDPs and cardiotoxic DiHOMEs accumulate aggravating the injury [75,118]. Therefore, future characterization of how IR injury alters the levels of these metabolites will provide more insight into the complex responses and pathobiology.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized the current study was limited by not directly assessing changes in the levels of epoxylipids (EETs, EDPs, EpOMEs) as well as the diol metabolites (DiHOMEs) in response to IR injury. However, it has been shown that cardiac ischemic insults decrease levels of the cardioprotective epoxylipids EETs and EDPs and cardiotoxic DiHOMEs accumulate aggravating the injury [75,118]. Therefore, future characterization of how IR injury alters the levels of these metabolites will provide more insight into the complex responses and pathobiology.…”
Section: Discussionmentioning
confidence: 99%
“…To verify the results of protein quantification, an enzyme activity investigation was conducted. Various compounds, such as epoxyeicosatrienoic acid ethanolamides [5], trans ‐stilbene oxide [10], 4‐nitrophenyl‐trans‐2,3‐epoxy‐3‐phenyl propyl carbonate [9], and EETs [24], have been used as the substrate of the epoxide hydrolases. In this study, the metabolic activity of total epoxide hydrolase in heart, liver, and kidney S9 samples was determined by the ring‐open hydrolysis reaction of 14,15‐EET.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain the total epoxide hydrolase activity of mEH and sEH in S9 samples, we performed an established in vitro study as described previously with a minor modification [24]. In brief, the S9 fraction was diluted to 0.012 mg/mL with PBS (0.1 M, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical value of Dantonic in the treatment of chronic stable angina pectoris was confirmed again by Phase III clinical trial of FDA. Previous studies showed that Dantonic treatment could significantly reduce the ischemia/reperfusion- (I/R-) and LAD induced myocardial damage and apoptosis, myocardial fibrosis, microcirculatory disturbance ( Zhao et al, 2010 ; Wei et al, 2013 ; Yang et al, 2013 ), oxidative stress, and inflammatory response ( Horie et al, 2005 ; Lee et al, 2013 ; Jun et al, 2014 ; Ren-an et al, 2014 ; Chen et al, 2016 ; Xu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%